Facade Media Sebagai Alternatif Titik Reklame Pembentuk Visual Kota Semarang - A Dicky Prastomo, SIP, MA (Soegijapranata Catholic University, 2019)
Simpang Lima, Pahlawan Street, Pemuda Street, Pandanaran Street, and Gadjah Mada Street now is becoming an important icon for Semarang City. The current condition shows that billboard arrangements in that area are uncluttered. More and more billboard will not make a good visual. This paper aims to provide alternative option for good vieweing in the city. A photographic survey is conducted to produce visual simulation using facade media. Relocation is needed from outside the street into building facade. The benefit using facade media will became an effective and efficient tool in the next future and expected to attract domestic or foreign tourist when visiting Semarang City. The simulation findings could give economic perpective to increase the local goverment’s revenue.